Design and analysis of retaining wall backfilled with shredded tire and subjected to earthquake shaking. Issue 90 (November 2016) - Shrestha, S.; Ravichandran, N.; Raveendra, M.; Attenhofer, J.A.
Abstract: The applicability of shredded tire as an economical alternative for conventional granular soil backfill for retaining walls was investigated by conducting geotechnical and structural designs as well as finite element simulations. A literature survey was conducted to compile and document the engineering properties of shredded tire. It was found that the key geotechnical engineering properties vary significantly with shred size and shredding method. Then, a gravity-cantilever retaining wall was designed for dynamic loading conditions considering seismic design parameters corresponding to the Charleston, SC area. Geotechnical design revealed a longer toe compared to heel for shredded tire backfill to maintain stability; however, a shorter footing was needed to maintain overall stability compared to that of granular backfill. Conventional designs and finite element simulations showed significant reductions in computed horizontal deflection at the tip of the wall, structural demand in terms of maximum shear force and bending moment, and construction cost in terms of excavation and material when shredded tire was used as the backfill. Upper and lower bound curves of maximum shear force and maximum bending moment in the stem were also produced based on the results of parametric studies conducted by varying the friction angle and cohesion of shredded tire, and the amplitude and mean period of the input motion. Highlights: A longer toe compared to heel is needed to maintain stability for shredded tire backfill. Structural demand for shredded tire backfill is less than that of conventional sand backfill. Significant construction cost (excavation plus materials) saving with shredded tire backfill.